2004
DOI: 10.1111/j.1365-2850.2004.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Judging the other: psychiatric nurses’ attitudes towards identified inpatients as measured by the semantic differential technique

Abstract: Nurses' attitudes towards psychiatric patients can be expressed in terms of either a symptom-oriented approach or a personhood-focused approach where the latter is characterized by the ambition to establish a genuine and lasting relationship, while the former places the emphasis on correcting 'defective' patient behaviour. To study whether previous typologies found in a qualitative in-depth interview study exist in a larger quantitative investigation and, if so, to identify and describe a structure for the nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
0
18
0
5
Order By: Relevance
“…According to Scheff (1999), stereotyped imagery of mental disorders is learned early in life, including the commonly held view that a person suffering from a mental disorder is potentially dangerous (Crisp, Gelder, Rix, Meltzer & Rowlands, 2000), unpredictable, and less intelligent than others (Angermeyer & Schulze, 2001). For example, patients diagnosed with borderline personality disorder diagnosis are stereotyped as ''difficult'' and ''demanding'' by staff (Gallop, 1988) and long-term schizophrenics can still be seen as ''empty shells'' without any ability to think, feel, or act (Davidson & Stayner, 1997), and are therefore judged by staff as being stupid, incompetent, or ignorant (Lilja, Ö rdell, Dahl & Hellzén, 2004). Nurses also tend to overrate their own importance when it comes to psychiatric patient's well-being (Lilja & Hellzén, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Scheff (1999), stereotyped imagery of mental disorders is learned early in life, including the commonly held view that a person suffering from a mental disorder is potentially dangerous (Crisp, Gelder, Rix, Meltzer & Rowlands, 2000), unpredictable, and less intelligent than others (Angermeyer & Schulze, 2001). For example, patients diagnosed with borderline personality disorder diagnosis are stereotyped as ''difficult'' and ''demanding'' by staff (Gallop, 1988) and long-term schizophrenics can still be seen as ''empty shells'' without any ability to think, feel, or act (Davidson & Stayner, 1997), and are therefore judged by staff as being stupid, incompetent, or ignorant (Lilja, Ö rdell, Dahl & Hellzén, 2004). Nurses also tend to overrate their own importance when it comes to psychiatric patient's well-being (Lilja & Hellzén, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Different studies have shown that nurses in psychiatric care have a strong tendency to use typologies in relation to the patients, leading to distanced relationships and to their not seeing the patient as an unique person (e.g. Lilja, Ö rdell, Dahl & Hellzén 2004). Foucault (2006) talks about a pessimistic perspective based on the carers' paternalistic view of the patients.…”
Section: Discussionmentioning
confidence: 98%
“…The results of two earlier studies (Lilja et al, 2004(Lilja et al, , 2006 indicated that in order to reach a deep enough understanding of the nurses' attitude, a new research strategy was needed. Consequently, a phenomenological-hermeneutic approach was used (Lindseth & Norberg, 2004) with the narrative picturing technique (Stuhlmiller, 1994) as a way of bringing to conscious awareness memories the body has stored.…”
Section: Narratives and Narrative Picturing Interviewsmentioning
confidence: 97%
“…Earlier in this project, nurses' attitudes have been described from a quantitative point of view. Findings showed that nurses had a strong tendency to use typologies in relation to the patients, leading to a distanced relationship and to their not seeing the patient as an unique person (Lilja, Ö rdell, Dahl, & Hellzén, 2004), and their having a strongly medical approach to their patients (Lilja, Hellzén, Lind, & Hellzén, 2006). To increase our understanding it is important to go further in our studies about attitudes and try to determine whether there is harmony or a discrepancy between nurses' and patients' view of the patient's former life, hospital stay and caring goals.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation